Frequency of Transfusion Transmitted Infections in Healthy Blood Donors in a Tertiary Care Hospital - Farhan Ahmed Shaikh, Aqsa Noureen, Abdul Rehman Khalil Shaikh, Sana Lund Baloch, Aisha Waqas, Rukhsana Saboor, Kiran Aamir, Aamir Ramzan (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine transfusion transmitted infectious disease (TTI) pattern in potential healthy replacement donors. Study Design: Cross sectional study Place and Duration: Diagnostic and Research Laboratory Liaquat University of Medical and Health Sciences Jamshoro, Hyderabad. Jan-2022-Dec 2022 Methods: Total 14,355 replacement donors of age 18-55 years were selected in this study as per inclusion criteria, which comprised of 25 questionnaire, evaluating donors for history of Injections, medicines, time since last donation, tattoos, not feeling well, dental work, sexual relationships, history of malaria / T.B, surgery, jaundice vaccination positive viral markers in the past followed by physical examination. SPSS 24.0 was used to analyze all data. Results: There were 9635 (67.1%) males and 4720 (32.95) females in this study. Among all, 42.8% cases had age 18-25 years, 26.8% cases had 26-30 years, 16.6% cases had 31-35 years and 13.7% patients were from age group 36-55 years. Majority of the donors 32.3% had blood group B positive, followed by O positive in 29.9%, 22% donors had A positive and AB positive blood group found in 8.7% cases. According to screening results, most common infection was Hepatitis B Core Antibody found in 10% cases, anti-HCV found in 2.17% cases, HBsAg in 0.3% cases, ICT malaria in 0.05% cases, RPR 0.41% and HIV 1&2 in 0.1% cases. Conclusion: HB core total antibody showed highest positivity in replacement donors despite stringent donor selection criteria, followed by Anti HCV. Syphilis, HBsAg, HIV and malaria showed lowest prevalences. Keywords: Blood Donors, HCV, HBV, ICT Malaria